Gastric Outlet Obstruction and Sigmoid Volvulus in a Patient with Pneumatosis intestinalis: An Etiology or a Complication. (10th July 2019) - Shaheen, Osama; Ahmad, Wassim; Mhammad, Najm Aldin
Abstract : Pneumatosis intestinalis (PI) is a radiographic finding which refers to the presence of gas within the wall of any part of the gastrointestinal tract. While in some cases it is an incidental finding which usually represent its benign nonischemic etiology, it may indicate a catastrophic intra-abdominal condition and distinctly characteristic of ischemic enterocolitis. Herein, we discuss the clinical signs and symptoms, the radiological features, the surgical management and outcome of an extremely rare concurrent triad of PI, gastric outlet obstruction, and the sigmoid volvulus based on a case of a patient who underwent surgery in our hospital, which, we think, can emphasize the mysterious concept of PI's mechanical etiology.